Análisis de emociones presentes en la elección de juegos tradicionales en niños de la Ludoteca Beru en la Comunidad Indígena de Zaragoza perteneciente al Departamento de Amazonas (2021)
The present investigation is entitled Emotions that intervene in the choice of games in children of the Beru Ludoteca in the Indigenous Community of Zaragoza belonging to the Department of Amazonas. The research seeks to describe the emotions that children have when they choose games in the toy library of the mission childhood association of the indigenous community of Zaragoza. The purpose of these foreign investment toy libraries in indigenous territory is to facilitate the integral development of children in addition to promoting the appropriation of custom and cultural practices through the development of their own toys. On this occasion, it was possible to establish the specific objectives that accompany said research work, the following actions to be carried out can be found: Carry out a review of the literature that identifies approximations of the emotions experienced by children from 6 to 8 years of age in the choice of games in the Beru (butterfly) Ludoteca of the indigenous community of Zaragoza, Design and apply an analytical matrix that identifies the emotions that intervene in the choice of game of the children of the Beru Ludoteca of the indigenous community of Zaragoza, Analyze the data obtained and elaborate the description of the results and Design a game rotation plan in the toy library.